Rancangan Sistem Informasi Perpustakaan Ruang Publik Terpadu Ramah Anak Berbasis Web - Firjatullah, Farhan; Febriandirza, Arafat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Child Friendly Integrated Public Space (RPTRA), is a facility built by the DKI provincial government to facilitate its citizens as well as a place that is friendly to children as well as a means of playground, one of the facilities provided is a library but the library still uses manual or conventional methods in the process so that many stages are still inefficient, therefore the implementation of this library system is a good suggestion for the creation of an efficient process in the library. This system was created using PHP and MySql with the waterfall method as a guideline, the use of this method is expected to simplify and speed up the design process on the Kalimati West Jakarta RPTRA library information system. The conclusion obtained from this research is the design of a web-based library system that is easy to use in terms of interface and usage experience and to build a library system that makes it easy to collect library inventory data in the Child Friendly Integrated Public Space (RPTRA).